2021
DOI: 10.3390/fermentation7040228
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Porous Biochar from Soapberry Pericarp at Severe Carbonization Conditions

Abstract: The residue remaining after the water extraction of soapberry pericarp from a biotechnology plant was used to produce a series of biochar products at pyrolytic temperatures (i.e., 400, 500, 600, 700 and 800 °C) for 20 min plant was used to produce a series of biochar products. The effects of the carbonization temperature on the pore and chemical properties were investigated by using N2 adsorption–desorption isotherms, energy dispersive X-ray spectroscopy (EDS) and Fourier-transform infrared spectroscopy (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…For SMB-300 and SMB-700were recorded as 0.056674 cmᶾ g-¹, and 0.1359 cmᶾ g-¹, respectively, as show in Table (1). These observations are consistent with the findings of [21], which indicates that raised the pyrolysis temperature develops pore properties, by discharging volatile organic materials, which leads to the destruction of the pore wall and raises the total pore volume within the biochar, which was consistent with their found [22]. Both SMB-700 and PFB-700 exhibit large surface area and total pore volume as well as numerous cavities on the surface making it a prime candidate for water and soil purification endeavors by adsorption of cationic chemicals and organic contaminants [23].…”
Section: Bet Surface Areasupporting
confidence: 89%
“…For SMB-300 and SMB-700were recorded as 0.056674 cmᶾ g-¹, and 0.1359 cmᶾ g-¹, respectively, as show in Table (1). These observations are consistent with the findings of [21], which indicates that raised the pyrolysis temperature develops pore properties, by discharging volatile organic materials, which leads to the destruction of the pore wall and raises the total pore volume within the biochar, which was consistent with their found [22]. Both SMB-700 and PFB-700 exhibit large surface area and total pore volume as well as numerous cavities on the surface making it a prime candidate for water and soil purification endeavors by adsorption of cationic chemicals and organic contaminants [23].…”
Section: Bet Surface Areasupporting
confidence: 89%
“…In contrast, this work performed the optimal biochar production at 900 • C for a residence time of 20 min. When compared to the previous study [45], it showed an abrupt increase in the BET surface area (14.1 and 277.1 m 2 /g, respectively) of soapberry pericarp-based biochar produced at 700 to 800 • C for a residence time of 20 min. On the other hand, the residence time also affected the pore properties of the resulting biochar products, which were produced at 900 • C by extending the residence time from 0 to 60 min.…”
Section: Yield and Pore Analysis Of The Resulting Biochar Materialscontrasting
confidence: 61%
“…As stated above, the use of fossil-based energy has been declining since its use causes climate changes and air pollution [32] and new solution need to be addressed to solve out this issue. An example is represented by the utilization of biochar that, due to its chemical and physical characteristics, can be used as a product itself or as an ingredient, within a mixed product for multiple objectives, including soil improvement, waste management, energy (or fuel) production, water pollution, and mitigation of climate change, as reported by Tsai et al [33].…”
Section: Processing Technologymentioning
confidence: 99%